Job Resourcefulness as a Moderator of the Work-Family Conflict - Job Satisfaction Relationship: A Study of Hotel Employees in Nigeria - Karatepe, Osman M. (Elsevier Science Bv, 2011)
The purpose of this study was to investigate job resourcefulness as a moderator of the effects of work-family conflict and family-work conflict on job satisfaction. Data were collected from a sample of frontline hotel employees in Abuja, the capital city of Nigeria. Hierarchical multiple regression analysis was employed to test the aforementioned relationships. Results demonstrated that the detrimental impacts of work-family conflict and family-work conflict on job satisfaction were weaker among frontline employees with higher job resourcefulness. Implications of the findings and directions for future research are offered.
Keywords: family-work conflict; hotel employees; job resourcefulness; job satisfaction; Nigeria; work-family conflict